(untitled) (Dermatology Reports, 2024)
This article presents a case study of a novel modification of the A-T flap, known as “Sorting Hat” flap, employed in dermatologic surgery for facial reconstruction. In the treatment of an 89-year-old male’s squamous cell carcinoma lesion on the forehead, the “Sorting Hat” flap, introduced as an innovative alternative, eliminates the need for Burrow triangles and relies on flap shape for inconspicuous scarring and favorable cosmetic outcomes.